Microwave-Assisted Enzymatic Extraction of Flavonoids from Armeniaca mume Sieb. Blossom and Their Immunomodulating Effect in Mice with DSS-Induced Colitis - Xinjun Yao; Jicheng Xu; Benu Adhikari; Weiqiao Lv (Molecules, 2021)
Armeniaca mume Sieb. blossom is among the traditional Chinese edible flowers, and it is widely used in the food and pharmaceutical industries. Flavonoids are among the most abundant bioactive compounds in A. mume Sieb. blossom. However, the research on the extraction of flavonoids from A. mume Sieb. blossom and their immunomodulating function is insufficient. In this study, we developed a microwave-assisted enzymatic extraction of flavonoids from A. mume Sieb. blossom (FAMB) and explored their immunomodulating effect on mice with dextran sulfate sodium salt-induced colitis. The results showed that the optimum parameters for microwave-assisted enzymatic extraction of FAMB were as follows: cellulase: 2.0%; microwave power: 200 W; microwave action time: 5 min; and enzymatic hydrolysis time: 50 min. FAMB significantly promoted the lymphocyte proliferation and natural killer (NK) cell killing activity in colitis mice, and increased the concentrations of TNF-α, IFN-γ, and IL-2 in serum. FAMB also significantly reduced the apoptosis of spleen lymphocytes in these mice. These results demonstrated that the microwave-assisted enzymatic method could significantly improve the yield and efficacy extraction of FAMB. FAMB showed a good immunomodulation effect on colitis mice.